2010
DOI: 10.1128/jb.01618-09
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptional Response ofLactobacillus caseiATCC 334 to Acid Stress

Abstract: This study investigated features of the acid tolerance response (ATR) inLactobacillus casei is an aciduric, rod-shaped, facultatively heterofermentative lactic acid bacterium (LAB) that can be isolated from a variety of environments including raw and fermented milk and meat or plant products, as well as the oral, intestinal, and reproductive tracts of humans and animals (24). Like other LAB species, L. casei produces lactic acid as a major end product of carbohydrate fermentation during growth, and strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 54 publications
9
150
3
2
Order By: Relevance
“…All of the metabolic reactions that result in the alkalisation of the cytosol of acidogenic organisms (such as those involved in the arginine deiminase (ADI) pathway, the citrate metabolism or else those involved in malolactic conversion) should be analysed in light of these novel findings. Indeed, and not surprisingly, all previous pathways act by subtracting protons from the cytoplasm and are strongly induced by an acidic environmental pH (Magni et al, 1999;Cotter & Hill, 2003;Broadbent et al, 2010). The conserved role of alkalising reactions across acidogenic bacteria is also supported by the data obtained for L. lactis IL1403-945 and S. pneumoniae SP292-945 in the presence of glucose and cellobiose as a carbon source (Arioli et al, 2010).…”
Section: Alkalising Reactions and Cell Bioenergeticssupporting
confidence: 67%
“…All of the metabolic reactions that result in the alkalisation of the cytosol of acidogenic organisms (such as those involved in the arginine deiminase (ADI) pathway, the citrate metabolism or else those involved in malolactic conversion) should be analysed in light of these novel findings. Indeed, and not surprisingly, all previous pathways act by subtracting protons from the cytoplasm and are strongly induced by an acidic environmental pH (Magni et al, 1999;Cotter & Hill, 2003;Broadbent et al, 2010). The conserved role of alkalising reactions across acidogenic bacteria is also supported by the data obtained for L. lactis IL1403-945 and S. pneumoniae SP292-945 in the presence of glucose and cellobiose as a carbon source (Arioli et al, 2010).…”
Section: Alkalising Reactions and Cell Bioenergeticssupporting
confidence: 67%
“…However, the increase in cyclopropane fatty acid production during [C 2 mim]Cl exposure demonstrates the distinct effect of ionic liquid on the bacterium. A number of studies using E. coli and lactobacilli have demonstrated that methylation of the cis-acyl chain double bond to form a cyclopropane ring plays a significant role in tolerance to acid, salt, butanol, and other stressors by reducing membrane fluidity and decreasing permeability (50)(51)(52)(53)(54). It is probable that cyclopropane fatty acid production plays a similar role in [C 2 mim]Cl tolerance by stabilizing the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…casei ATCC 334 and Lb. johnsonii NCC 533 showed a significant increase in the ratio of saturated to unsaturated membrane fatty acids (122,467). In the latter strain, the membrane fatty acid composition (and in particular the saturation level) is associated with changes in cell survival during heat or acid shock.…”
Section: Stress Associated With Intestinal Transitmentioning
confidence: 99%
“…lactis (121) and Lb. casei (122) and in a number of stress conditions in E. faecalis (123,124), S. mutans (125), and S. pneumoniae (126). A number of studies have shown that RSH is mainly involved in the classical SR, whereas the small synthetases may play different roles.…”
Section: The Stringent Response: the Ribosome As A Sensormentioning
confidence: 99%